2019
DOI: 10.9734/ijpr/2019/v3i230089
|View full text |Cite
|
Sign up to set email alerts
|

Mycoflora and Nutritional Analysis of Smoked Dried Crayfish (Penaeus monodon – Prawns) During Storage

Abstract: This study was carried out to investigate the mycoflora and nutritional composition of smoked dried crayfish Penaeus monodon (prawns) during storage for twenty-four weeks. The mycoflora were isolated at four weeks interval using direct plating and dilution methods on Potato Dextrose Agar (PDA), Saboraud Dextrose Agar (SDA) and Malt Extract Agar (MEA). The fungi isolated using direct plating methods and dilution methods were Aspergillus niger, Aspergillus flavus, Aspergillus fumigates, Rhizopus sp., Phytophthor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The total different species fungi isolated from stored groundnut was 68.3% higher that work reported by Tobin-West et al [12] in four major markets in Port Harcourt, Nigeria, and Fagbohun and Faleye [13] as they reported 65.1% and 60.0% respectively. The occurrence of fungi was high in Old market than from any other location sampled this may be due to activities of the people storing it or from different farms the groundnut was planted and harvested because fungi is a major organisms that infect groundnut [14].…”
Section: Discussionmentioning
confidence: 51%
“…The total different species fungi isolated from stored groundnut was 68.3% higher that work reported by Tobin-West et al [12] in four major markets in Port Harcourt, Nigeria, and Fagbohun and Faleye [13] as they reported 65.1% and 60.0% respectively. The occurrence of fungi was high in Old market than from any other location sampled this may be due to activities of the people storing it or from different farms the groundnut was planted and harvested because fungi is a major organisms that infect groundnut [14].…”
Section: Discussionmentioning
confidence: 51%
“…An experiment was performed on stored groundnut seeds, and it was found that a total of seven pathogenic fungal species A. flavus , A. fumigatus , A. niger , Rhizopus , Mucor , Penicillium , and Fusarium were identified. These pathogenic fungi cause contamination and reduce the nutritional value, edibility, and marketability of groundnut, ultimately affecting the agricultural economy . Soil-borne opportunistic A. flavus pathogen infection deteriorates the groundnut seed quality by decreasing its nutritional value, such as lowering the oil content and increasing unsaturated fatty acids that lead to reduced edibility and marketability .…”
Section: Effect Of Aflatoxins On Oil Quality Of a Hypogaeamentioning
confidence: 99%
“…These pathogenic fungi cause contamination and reduce the nutritional value, edibility, and marketability of groundnut, ultimately affecting the agricultural economy. 36 Soil-borne opportunistic A. flavus pathogen infection deteriorates the groundnut seed quality by decreasing its nutritional value, such as lowering the oil content and increasing unsaturated fatty acids that lead to reduced edibility and marketability. 37 One of the studies was performed to check the relationship between stored groundnut seed quality and A. flavus infection, and the outcomes demonstrated that the seeds that are inoculated with 0.25% fungal infection maintained their germination growth up to 71%, hence suggesting that this level could be an acceptable and permissible limit for the appropriate storage of seeds.…”
Section: Effect Of Aflatoxins On Oil Quality Of a Hypogaeamentioning
confidence: 99%